Kurkumin Aerosol dengan Media Nasal Spray sebagai Terapi Preventif dan Kuratif Penderita Alzheimer - Nabila Rayhan Yasmin; Rr Astri Nur Azizah Utama; Mukhlis Imanto (MAJORITY, 2021)
Alzheimer is a neurodegenerative disease which is the third leading cause of death for elderly in the world. Until now, no effective therapeutic management has been found for Alzheimer's patient. Curcumin is known to have powerful antioxidant, anti-inflammatory, and anti-amylogenic properties so it has the potential to prevent and treat Alzheimer's disease. A review of the journals obtained using search engines such as Google Scholar, Proquest, Sciencedirect, NCBI, PubMed, and Springer were conducted with a publication year spanning 2011-2021. The journals obtained are then selected to obtain valid and reliable journals. Then a literature review and article writing are conducted. Curcumin has the ability to inhibit the formation and spread of free radicals, affect the work of macrophages in cleaning β-amyloid plaque, reduce the production of proinflammatory cytokines, and mainly inhibit the accumulation and aggregation of β-amyloid. Curcumin needs to be distributed appropriately in order to have its maximum therapeutic effect. Aerosol-based delivery of curcumin has been shown to deliver most of the therapeutic compounds to the brain without causing systemic toxicity or drug degradation in the liver. The use of nasal spray media can support the delivery of aerosol curcumin via the nasal route because it can transport drugs through the brain more efficiently. Aerosol curcumin with nasal spray device has the potential as a preventive and curative therapy for Alzheimer's disease